End of watch [videorecording (DVD)] - Ayer, David; Ayer, David; Ayer, David; Gyllenhaal, Jake, 1980-; Peña, Michael, 1976-; Kendrick, Anna (Universal Studios Home Entertainment, 2013)
Two young officers are marked for death after confiscating a small cache of money and firearms from the members of a notorious cartel, during a routine traffic stop.